Canalisation in the wild: effects of developmental conditions on physiological traits are inversely linked to their association with fitness. (30th March 2018) - Boonekamp, Jelle J.; Mulder, Ellis; Verhulst, Simon
Abstract: Ecological conditions affect fitness, but mechanisms causing such effects are not well known, while evolved responses to environmental variation may depend on the underlying mechanisms. Consequences of environmental conditions vary strongly between traits, but a framework to interpret such variation is lacking. We propose that variation in trait response may be explained by differential canalisation, with traits with larger fitness effects showing weaker responses to environmental perturbations due to preferential resource allocation to such traits. We tested the canalisation hypothesis using brood size manipulation in wild jackdaw nestlings in which we measured eight physiological traits (mainly oxidative stress markers), and two feather traits. For each trait, we estimated manipulation response and association with fitness (over‐winter survival). As predicted, a strong negative correlation emerged between manipulation response and association with fitness ( r =−0.76). We discuss the consequences of differential trait canalisation for the study of mechanisms mediating environmental effects on fitness.